The Relationship Between Work Motivation And Work Readiness Of Participants Taking Part In Mtu Based Sewing Training At Blk Padang Panjang - Putri Wulandari; Lili Dasa Putri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research was motivated by investing in the relationship between work motivation and work readiness of participants who took part in sewing training based on the Mobile Training Unit at the Padang Panjang Job Training Center. This research is a quantitative and correlational approach. The population of this study were all sewing training participants in 2023 with a total of 64 participants and they had completed the training from February to April for 6 meetings. Researchers used the Cluster Random Sampling method. With a sample size of 50% of the population. The number of training participants in 2023 will be 64 training participants, while the population that will be taken will be 32 training participants. The data collection tool is a questionnaire, and the data collection technique is a questionnaire. And the techniques used in data analysis are the percentage formula and the Product Moment correlation formula. The research results show that: 1) The work motivation of participants taking part in mobile training unit-based sewing training at the Padang Panjang Job Training Center (BLK) is relatively low, this is shown by the respondents' statements in the research instrument which are dominated by infrequent answers, 2). The work readiness of participants who took part in sewing training based on the Mobile Training Unit at the Padang Panjang Job Training Center (BLK) was categorized as less ready, this can be seen from the statements filled in by respondents in the research instrument which was dominated by rare answers, 3). There is a relationship between work motivation and work readiness of participants taking part in mobile training unit-based sewing training at the Padang Panjang Job Training Center (BLK). because the rxy value: 0.887 > 0.349, and the significance value: 0 < 0.05, which means there is a relationship. The results of data analysis show that there is a significant positive relationship between work motivation and work readiness. Participants who have high work motivation tend to have a better level of work readiness.